IMPACT OF PROTEIN AND PROBIOTIC SUPPLEMENTATION ON IMMUNITY AND SURVIVAL OF Clarias gariepinus UNDER PATHOGEN CHALLENGE IN AQUACULTURE - Admasu, Firew; Wakjira, Mulugeta; Bayissa, Tokuma Negisho; Bacha, Ketema (Agency for Marine and Fisheries Extension and Human Resources, 2025)
Bacterial infections, particularly those caused by Pseudomonas aeruginosa, pose a threat to aquaculture and lead to economic losses in African catfish (Clarias gariepinus). This study evaluates the effects of dietary protein and probiotic supplementation on fish health, growth performance, and survival following P. aeruginosa infection, using both in vitro and in vivo approaches. The in vitro assays determined the infective dose of P. aeruginosa and its interactions with probiotics. At the same time, in vivo trials assessed survival, behavioral responses, feed utilization efficiency, and pathological changes over 72 hours. Furthermore, fish were fed varying protein levels (35%, 40%, and 45%) and probiotic concentrations (1:2:3 ratio) for two months before being challenged with bacteria. Higher protein (40–45%) and probiotic supplementation (2–3 mL) significantly improved survival rates (up to 83.33%), reduced weight loss, and mitigated organ damage as opposed to groups with lower supplementation (50% survival), though lower than the uninfected controls (100% survival). The improved survival and reduced pathological damage in probiotic-supplemented fish suggest a potential enhancement of immune defense mechanisms and overall physiological resilience. Probiotics have been reported to modulate immune responses by promoting beneficial microbiota, competing with pathogens, and supporting host immunity, which may contribute to the observed protective effects. Additionally, probiotic-fed groups exhibited improved water quality with lower accumulation of nitrogenous waste in infected tanks. These findings suggest that protein- and probiotic-enriched diets enhance disease resilience, feed efficiency, and water quality in aquaculture, supporting sustainable fish production through nutritional and health improvement. Future research is recommended to investigate immune-related biomarkers to better understand the immune-modulatory effects of these dietary interventions.